Antimicrobial Blue Light Inactivation of Polymicrobial Biofilms - Ferrer-Espada, Raquel; Liu, Xiaojing; Goh, Xueping Sharon; Dai, Tianhong (Frontiers in Microbiology, 2019)
Polymicrobial biofilms, in which mixed microbial species are present, play a significant role in persistent infections. Furthermore, polymicrobial biofilms promote antibiotic resistance by allowing interspecies transfer of antibiotic resistance genes. In the present study, we investigated the effectiveness of antimicrobial blue light (aBL; 405 nm), an innovative non-antibiotic approach, for the inactivation of polymicrobial biofilms. Dual-species biofilms with Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus (MRSA) as well as with P. aeruginosa and Candida albicans were reproducibly grown in 96-well microtiter plates or in the CDC biofilm reactor for 24 or 48 h. The effectiveness of aBL inactivation of polymicrobial biofilms was determined through colony forming assay and compared with that of monomicrobial biofilms of each species. aBL-induced morphological changes of biofilms were analyzed with confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). For 24-h old monomicrobial biofilms formed in 96-well microtiter plates, 6.30-log10 CFU inactivation of P. aeruginosa, 2.33-log10 CFU inactivation of C. albicans and 3.48-log10 CFU inactivation of MRSA were observed after an aBL exposure of 500 J/cm2. Under the same aBL exposure, 6.34-log10 CFU inactivation of P. aeruginosa and 3.11-log10 CFU inactivation of C. albicans were observed, respectively, in dual-species biofilms. In addition, 2.37- and 3.40-log10 CFU inactivation were obtained in MRSA and P. aeruginosa, dual-species biofilms. The same aBL treatment of the biofilms developed in the CDC-biofilm reactor for 48 h significantly decreased the viability of P. aeruginosa monomicrobial and polymicrobial biofilm when cocultured with MRSA (3.70-and 3.56- log10 CFU inactivation respectively). 2.58-log10 CFU inactivation and 0.86-log10 CFU inactivation was detected in MRSA monomicrobial and polymicrobial biofilm when cocultured with P. aeruginosa. These findings were further supported by the CLSM and SEM experiments. Phototoxicity studies revealed a no statistically significant loss of viability in human keratinocytes after an exposure to 216 J/cm2 and a statistically significant loss of viability after 500 J/cm2. aBL is potentially an alternative treatment against polymicrobial biofilm-related infections. Future studies will aim to improve the efficacy of aBL and to investigate aBL treatment of polymicrobial biofilm-related infections in vivo.